Creating relational ripples in therapy - Karamatsouki, Marilena (Murmurations: Journal of Transformative Systemic Practice, 2022)
Exegesis In my doctoral inquiry, I focused on the relational space in the therapy room. The relational space is a concept that may appear in different forms and include words, emotions, non-verbal communication, objects within the context of space and time (Gergen, 2015). As a systemic practitioner and practitioner researcher, I find the process, and, potentially, the outcome of therapy to be largely defined by: the relational space between myself and my client; the relational space within my different selves; and the interconnectedness of these relational spaces. By being both self-reflexive and relationally reflexive, my research addresses the question of how the relational space between client and therapist interconnects with the relational space within the therapist, thus creating “relational ripples” in the therapy room (Karamatsouki, 2020). My interest in the area emerged as in my practice I observed that when I bring more of myself in the therapy room, more of the client is in there, too. In order to study the complex encounter in the therapy room I used autoethnography through storywriting. Autoethnography, “an autobiographical genre of writing and research that displays multiple layers of consciousness” (Ellis, 2004, p. 37), gives access to research material from an insider’s perspective. I use stories from practice in a literary style and in an ethical manner, where the focus is neither on the therapy techniques nor on the client’s difficulties. Instead, the focus is on the relational conversation between my client and me, as well as my inner dialogue and thoughts and feelings. What follows in a story from within practice which appears in my doctoral thesis and shows the relational flow of the therapeutic process and the creation of relational ripples. In a way, what I am trying to do is expand systemic thinking by bringing to the fore the relational space within myself as a therapist and create a professionally employable space for the personal.